Lateral canal peripheral positional vertigo diagnosis: a neurophysiological approach - Zuma E Maia, Francisco Carlos; Ramos, Bernardo Faria; Castillo-Bustamante, Melissa; Cal, Renato Valerio; Madrigal, Jorge (Frontiers in Neurology, 2025)
Lateral semicircular canal peripheral positional vertigo (LC-PPV) is a common condition, even though accurate determination of the affected side remains a diagnostic challenge that is crucial for effective treatment. The aim of this study is to provide a systematic diagnostic approach for lateralization in LC-PPV, based on analysis of endolymphatic flow dynamics elicited by the Bow and Lean test and supine roll test.